Qur’anic, Sufistic, and Philosophical Foundations of a Love-Based Curriculum: A Comparative Analysis of Ibn ‘Arabī and al-Fakhr al-Rāzī - Ikhlas Budiman; Otong Surasman; Zakaria Husin Lubis; Jun Firmansyah; Mulyani Mulyani (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2026)
This study investigates the concept of love in the works of Ibnu Arabi and al-Fakhr al-Rāzī to elucidate the Qur’anic, Sufistic, and philosophical foundations of the Love-Based Curriculum (KBC). The research seeks to develop an integrative model by analyzing Ibn ‘Arabī’s Sufi-metaphysical perspective and al-Rāzī’s philosophical-exegetical approach, as well as their respective contributions to the KBC. Employing qualitative library research, the study analyzes data using content and comparative methods. The comparative analysis centers on the five pillars of the love-based curriculum: (1) love of God and His Messenger, (2) love of knowledge, (3) love of the environment, (4) love of oneself and others, and (5) love of the homeland. The findings indicate that Ibn ‘Arabī conceptualizes love as an ontological principle of divine self-disclosure (tajallī) that connects al-ḥaqq and creation, while al-Rāzī interprets love within a rational, psychological, and ethical framework aimed at human perfection. Although their approaches differ, both thinkers assert that love is intrinsic to the structure of existence and the primordial nature (fiṭrah) of humanity. This convergence is evident in their epistemological, ecological, social, and spiritual perspectives. Consequently, the KBC is presented as a transformative model that integrates Qur’anic, Sufi, and philosophical sources to foster spiritual awareness, ethical responsibility, ecological consciousness, and social harmony by establishing love as a foundational principle in education and human development.